El rey de los gigoló - Vallejo Knockaert, José Miguel ([Santiago, Chile] : Edición Digital, 2013)
A young Cuban discovers he is irresistible to women and is determined to become the best of gigolo in New York during the crazy 90s.
Online resource; title from PDF title page (Digitalia, viewed October 29, 2016)
Keywords: Male prostitutes -- Fiction; New York (N.Y.) -- Fiction; Humorous fiction; Electronic books